Rare cancer with primary pleural epithelioid hemangioendothelioma diagnosed by thoracoscopic biopsy achieving disease control after 16 months: case report and literature review - Pateras, Ioannis S.; Kostopanagiotou, Konstantinos; Samaras, Menelaos G.; Koumarianou, Anna; Koutrouli, Mina; Korodimos, Nikolaos; Kampoli, Katerina; Apollonatou, Vasiliki; Manali, Effrosyni; Loukides, Stylianos; Tomos, Periklis; Tsiodras, Sotirios; et al. (Frontiers in Pharmacology, 2024)
Epithelioid hemangioendothelioma (EHE) is a rare malignant vascular tumor. Pleural EHE (pEHE) is even more uncommon, with significant heterogeneity in clinical behavior, challenging diagnosis and treatment decisions. Herein, we present a 74-year-old woman admitted to the hospital with dyspnea, pleural effusion, and refractory euvolemic hyponatremia. Chest computed tomography revealed a large right-sided pleural effusion with irregular thickening of the parietal pleura and localized nodularity. Histologic evaluation of thoracoscopic pleural biopsy tissue confirmed the diagnosis of pEHE. Assessment of volume status suggested that hyponatremia was attributed to a paraneoplastic endocrine syndrome. Administration of the multi-target tyrosine kinase inhibitor Pazopanib was associated with disease control with the patient remaining free-of symptoms after 16 months of follow-up. This report adds to the knowledge base of this exceptionally rare entity highlighting the need for a multi-disciplinary approach.